The neighborhood as an energy-generating community: the case of the El Banafseg residential neighborhood, East Cairo - Helmy, Mona; Micheal, Amany (Frontiers in Built Environment, 2023)
Nowadays, energy consumption is a global challenge. This is due to the shortage of several energy sources, and consequently, to their increasing prices. This paper argues that by using an integrative approach for using various energy harvesting techniques, a typical residential neighborhood can be operated as a self-generator of its needed energy, or part of it. The paper follows a mixed qualitative, experimental, and numerical simulation approaches to examine the practicality of the paper hypothesis. It uses Space syntax modeling theory (a socio-spatial software) to analyze the pedestrian flow to indicate the potential locations of the kinetic energy harvesting Piezoelectric tiles in the selected residential neighborhood. Moreover, the availability of installation of Photovoltaic electrical cells on rooftops of the neighborhood residential blocks is studied. The numerical simulation part quantifies the capacity of the harvested energy to reach a model of a green neighborhood. The paper measures the percentage of the residences’ energy needs that can be harvested using renewable energy resources. It reveals that 30% of the energy consumed in the residential blocks can be generated from Photovoltaic electrical cells. Moreover, 38% of the energy consumption through the light poles of the entire neighborhood can be generated using the kinetic energy harvested by the Piezoelectric tiles.